Persistent memories of long-term potentiation and the N-methyl-d-aspartate receptor. (May 2019) - Bliss, TVP; Collingridge, GL
In this article, we describe our involvement in the early days of research into long-term potentiation. We start with a description of the early experiments conducted in Oslo and London where long-term potentiation was first characterised. We discuss the ways in which the molecular pharmacology of glutamate receptors control the induction and expression of long-term potentiation and its counterpart, long-term depression. We then go on to summarise the extraordinary advances in understanding the cellular mechanisms of synaptic plasticity that have taken place in the subsequent half century. Finally, the increasing evidence that impaired long-term potentiation is a core feature of many brain disorders (LToPathies) is addressed by way of a few selected examples.